Penile cutaneous horn-a rare case - Dinesh Kumar Barolia; Deepak Sethi; Anjali Sethi; Ram Jamana; Shanker Meena; Pinky Rachhoya (International Journal of Medical Research and Review, 2015)
Penile cutaneous horn is a horn like hyper-keratotic lesion over penis which is an unusual site and a rare case. We report a case of cutaneous horn of penis in age of 20 years which is also a rare presentation in this age group.